Hydrogeochemical Characterization and Therapeutic Zoning of Low-Enthalpy Geothermal Hot Springs in Mexico: Implications for Wellness Tourism and Sustainable Resource Management - Puy-Alquiza, María J.; Puy, Miren Y.M.; Salazar-Hernández, Ma. D.C.; Prol-Ledesma, Rosa Maria; Zubia, Velia Y.O. (Global Journal of Earth Science and Engineering, 2025)
This study aims to characterize the geochemical composition of low-enthalpy thermal waters in Mexico and to evaluate their therapeutic potential and sustainable applications, establishing a scientific and territorial framework for integrated resource management. Data were compiled from hot springs distributed across 21 Mexican states, covering the period from 1975 to 2024. The analysis integrates hydrogeochemical databases from academic and governmental sources, complemented by technical reports, satellite imagery, and cartographic tools (Google Maps and Canvas X GIS 11). A total of 21 thematic maps were developed to illustrate the spatial distribution of thermal mineral water types (sulfurous, ferruginous, bicarbonate, calcium, and magnesium), temperature ranges, functional classifications, and levels of tourism development. The results indicate that minerals such as sulfur, iron, calcium, and bicarbonate contribute to well-documented therapeutic effects related to dermatological, musculoskeletal, digestive, and respiratory treatments. Comparative analysis with previous hydrothermal studies confirms Mexico’s exceptional geothermal diversity and rich cultural heritage, while also highlighting persistent challenges related to conservation, regulation, and sustainable resource management. Overall, this research highlights Mexican thermal waters as a valuable natural and cultural geothermal heritage and advocates their sustainable use through thermal routes, therapeutic centers, and territorial planning strategies that integrate human health, environmental conservation, and community participation. The findings provide a solid scientific foundation for future geothermal policy development and wellness-oriented georesource management.